2011
DOI: 10.1038/ismej.2011.152
|View full text |Cite
|
Sign up to set email alerts
|

Analogous nutrient limitations in unicellular diazotrophs and Prochlorococcus in the South Pacific Ocean

Abstract: Growth limitation of phytoplankton and unicellular nitrogen (N2) fixers (diazotrophs) were investigated in the oligotrophic Western South Pacific Ocean. Based on change in abundances of nifH or 23S rRNA gene copies during nutrient-enrichment experiments, the factors limiting net growth of the unicellular diazotrophs UCYN-A (Group A), Crocosphaera watsonii, γ-Proteobacterium 24774A11, and the non-diazotrophic picocyanobacterium Prochlorococcus, varied within the region. At the westernmost stations, numbers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
83
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 64 publications
10
83
4
Order By: Relevance
“…This hypothesis is consistent with the similarity in responses of diazotrophs and Prochlorococcus HL spp. to Fe addition, both in this study and in a study in the Southwest Pacific Ocean (Moisander et al, 2012).…”
Section: Relief From Fe Limitation In Oligotrophic Taxasupporting
confidence: 63%
“…This hypothesis is consistent with the similarity in responses of diazotrophs and Prochlorococcus HL spp. to Fe addition, both in this study and in a study in the Southwest Pacific Ocean (Moisander et al, 2012).…”
Section: Relief From Fe Limitation In Oligotrophic Taxasupporting
confidence: 63%
“…The significant negative correlation observed between silicate and UCYN-A1 and γ-24774A11 transcripts, and UCYN-A1 and fucoxanthin, could be indicative of shifting phytoplankton communities between the ATS and Coral Sea, given that UCYN-A is known to live in association with a prymnesiophyte host (Thompson et al, 2012;Hagino et al, 2013;Krupke et al, 2013). Currently, the lifestyle (for example, free-living, particle attached or symbiont) of γ-24774A11 remains unknown (Langlois et al, 2015); however, it has been speculated that it may depend upon phytoplankton-produced dissolved organic carbon (Moisander et al, 2012(Moisander et al, , 2014. Although strongly co-linear variables were removed from our analyses, silicate was inversely correlated to salinity and positively correlated to temperature, therefore it could also be indicative of a water mass tracer rather than a biological causation.…”
Section: Arafura Sea Coral Seamentioning
confidence: 99%
“…Therefore, other factors may have had a significant influence on diazotroph distribution and activity, for instance, dissolved iron (dFe) availability is known to limit marine N 2 fixation (see Sohm et al, 2011) and dFe additions can stimulate diazotrophic activity (Moisander et al, 2012;Turk-Kubo et al, 2012). In the western South Pacific ocean, Moisander et al, (2012) demonstrated that the abundances of unicellular diazotrophs, including UCYN-A and γ-24774A11, not only increased substantially in response to dFe amendments but also exhibited signs of iron and phosphorous co-limitation.…”
Section: Arafura Sea Coral Seamentioning
confidence: 99%
See 1 more Smart Citation
“…The physiology or genome content 531 of these taxa remains completely unknown, but they seem to be abundant in warm, oligotrophic 532 surface waters globally (Langlois et al, 2005). In the southwestern Pacific, the abundance of this 533 group has been shown to be correlated to DOC concentration, and to increase with Fe and P 534 addition (Moisander et al, 2012). In contrast, the dominant diazotroph in the CCE was an OTU 535 sharing 95 % NifH amino acid identity with Trichodemsium erythraeum (OTU181) and OTUs 536 matching Candidatus Atelocyanobacterium thalassa (UCYN-A; OTU1321 and OTU50).…”
Section: Simper)mentioning
confidence: 99%